Students Starting University: Exploring Factors That Promote Success for First-Year International and Domestic Students - Smith, Steven M.; Carter-Rogers, Katelynn; Norris, Meghan E.; Brophy, Tom (Frontiers in Education, 2022)
There are many factors that influence the first-year university student experience, and these factors can vary depending on student characteristics. In this research, using survey data, we explore differences between domestic Canadian and international (non-Canadian) first year university students across four categories that have been identified in past research. These categories broadly influence student success: individual factors, psychological needs, social relationships and connections to campus, and beliefs about and commitment to academics. 272 students (domestic: N = 185, international: N = 86) responded to quantitative individual difference items. International students reported greater drive, higher self-esteem, and placed greater importance on strong social networks, social life, and faith. Further, as compared to domestic first-year students, international students reported higher campus engagement, greater preferences for textbooks and online tutorials, being alone with their thoughts, higher confidence with their major choice, and reported studying more. Importantly, international students were less likely to feel they had a safe place to live in comparison to domestic students (all p <. 05). These data show that international students come to campus with differential needs, styles, and experiences, which can inform approaches taken by institutions in supporting their students’ success.